Smoke Behavior and Exercise Duration: Analysis Blood Pressure Increase of Badminton Player - Mayasari, Ema (Journal of Global Research in Public Health, 2017)
Background: Blood pressure increase is one of many thing that can be a trigger of infark miocard acute. Now people who play sport also be a smoker. Duration of sport as such burdening heart, moreover with smoke behavior. Certainly it make a serious problem for heart. The purpose of this research to find there is influence of smoke behavior and duration exercise with blood pressure increase. Method: This research is observational with cross sectional approach, sample use simple random sampling 63 people, type of data involve respondent characteristic, smoke behavior, exercise duration, blood pressure increase, with use questioner and observational paper. This research use logistic regression. Result: The result of cross tabulation that most of the rsponden who smoke had a increase blood pressure there is 47 people (74,61%), most of the responden who short exercise duration had increase blood pressure there is 41 people (65,08%). Analyze of statistic say there is influence smoke behavior to increase blood pressure (p value 0,000 < Î± 0,05). There is no influence exercise duration to increase blood pressure (p value 0,174 > Î± 0,05). Overall shows there is influence smoke behavior and exercise duration to increase blood pressure (p value 0,000 < Î± 0,05). Conclusion: Based on result there is influence smoke behavior to increase blood pressure because most of respondent had a long history of smoke who this fact make artery became a narrow, so that pressure of blood flow will be increase. While there is no influence exercise duration to increase blood pressure because the increase more caused from stress and mindset of badminton players who must to be winner in that game.